An improved trusted method for global congestion price computing based on software defined networking in data-centred network. (2018) - Chun, Shan; Xiao-Long, Chen
The past computing method of the link status price is difficult to meet the needs of dynamic network. This paper is presented to take full advantage of the feature that the global link status information can be grasped by the central controller of software defined networking (SDN) architecture and proposed a two-tier trusted method for global congestion price computing (GCPC). The ratio argument vector B is given by the upper-tier method with the machine learning algorithm and fuzzy C-means clustering algorithm according to the global network operating status information. The link status price is computed according to ratio argument vector B . The simulation results show that the link status price calculated by GCPC method is trusted and this improved method can efficiently promote the throughput of bisection bandwidth.